Metal artifact reduction in MRI-based cervical cancer intracavitary brachytherapy. (17th March 2017) - Rao, Yuan James; Zoberi, Jacqueline E; Kadbi, Mo; Grigsby, Perry W; Cammin, Jochen; Mackey, Stacie L; Garcia-Ramirez, Jose; Goddu, S Murty; Schwarz, Julie K; Gach, H Michael
Abstract: Magnetic resonance imaging (MRI) plays an increasingly important role in brachytherapy planning for cervical cancer. Yet, metal tandem, ovoid intracavitary applicators, and fiducial markers used in brachytherapy cause magnetic susceptibility artifacts in standard MRI. These artifacts may impact the accuracy of brachytherapy treatment and the evaluation of tumor response by misrepresenting the size and location of the metal implant, and distorting the surrounding anatomy and tissue. Metal artifact reduction sequences (MARS) with high bandwidth RF selective excitations and turbo spin-echo readouts were developed for MRI of orthopedic implants. In this study, metal artifact reduction was applied to brachytherapy of cervical cancer using the orthopedic metal artifact reduction (O-MAR) sequence. O-MAR combined MARS features with view angle tilting and slice encoding for metal artifact correction (SEMAC) to minimize in-plane and through-plane susceptibility artifacts. O-MAR improved visualization of the tandem tip on T2 and proton density weighted (PDW) imaging in phantoms and accurately represented the diameter of the tandem. In a pilot group of cervical cancer patients ( N   =  7), O-MAR significantly minimized the blooming artifact at the tip of the tandem in PDW MRI. There was no significant difference observed in artifact reduction between the weak (5 kHz, 7 z -phase encodes) and medium (10 kHz, 13 z -phase encodes) SEMAC settings. However, the weak setting allowed a significantly shorter acquisition time than the medium setting. O-MAR also reduced susceptibility artifacts associated with metal fiducial markers so that they appeared on MRI at their true dimensions.